An Integrated Approach for Analysis of Higher Penetration of Variable Renewable Energy: Coupling of the Long-Term Energy Planning Tools and Power Transmission Network Models - Verica Taseska-Gjorgievska; Miko Todorovski; Natasa Markovska; Aleksandar Dedinec (Journal of Sustainable Development of Energy, Water and Environment Systems, 2019)

(untitled)
Many studies and scientific papers have been published that consider the integration of renewable sources in energy systems, using the least-cost optimization models as a long-term generation expansion planning tool. Supplementary to these analyses, this paper focuses on the transmission network capacity for acceptance of variable renewable energy. The hypothesis is that the simplified electric power transmissions system in the long-term planning modelling tools does not reflect properly the capacity for integration of the variable renewable energy. An integrated approach is applied with aim to incorporate the grid expansion needs and costs (using direct current load flow analysis), necessary for increased renewable electricity penetration. The already developed MARKAL-Macedonia model will be used as a case study. After several iterations and feedback loops between the MARKAL-Macedonia and the network model, the expected outcome is to achieve a new cost-effective solution for deployment of variable energy on a larger scale.